DETERMINATION OF PRIORITY OF CYBER SECURITY MEASURES AT INCOMPLETE EXPERT RANKINGS (Information systems and technologies security, 2020)
High-quality functioning of the information security system and solving problems that arise in the information protection, is currently a topical trend in various areas of human life. Successful cyber protection consist in creating and implementing a multi-level system of measures that cover various aspects with complex interact and complement each other. These measures have a different nature, and their priorities may differ significantly in terms of different services of the organization, so it is logical to formalize the sequence of cybersecurity implementation in a class of group choice tasks. The paper proposes a flexible mathematical apparatus for modeling information security problems and adequate application of the opinion analysis of experts’ team in practice. The approach to finding the resultant ranking of measures priority is described as a solution to the problem of multicriteria optimization, where the sequence of measures implementation may involve the interaction of performers and require regulation of theactions sequence of all elements and subsystems of the organizational system. This approach allows to combine different information security measures proposed by the experts of various departments; to find a compromise solution for a diverse group of experts; not to violate any expert's preferences under calculating the compromise ranking of cyber security measures. The proposed approach can be useful in developing appropriate cybersecurity measures and favorable in developing and implementing of rapid response procedures to threats, as well as it can be indispensable in the overall building or improving organization security system and it can contain elements of training, coordination, and complexity of expert team members, who are the heads of units of a single organizational system.
Keywords: organisational system; information security; metric; distance; median; group ordering objects; incomplete expert ranking